PEŁNIĆ SŁUŻBĘ BOGU I POLSCE. ŚWIĘTEJ PAMIĘCI PREZYDENTA RYSZARDA KACZOROWSKIEGO (1919-2010) - Godek, Sławomir (Zeszyty Prawnicze, 2016)
PEŁNIĆ SŁUŻBĘ BOGU I POLSCE. ŚWIĘTEJ PAMIĘCI PREZYDENTA RYSZARDA KACZOROWSKIEGO (1919-2010)